Low Level of Her-2 Locus Amplification by Fluorescent In Situ Hybridization Does Not Correlate with Her-2 Protein Overexpression by Immunohistochemistry in Barrett's Esophagus. (6th May 2010) - Rygiel, Agnieszka M.; Milano, Francesca; ten Kate, Fiebo J.; Bergman, Jacques J. G. H. M.; Krishnadath, Kausillia K.
Abstract : An accurate evaluation of the Her-2 status has important prognostic and therapeutic implications in many carcinomas. The aim of the study was to correlate Her-2 locus (17q11.2) amplification and chromosome 17 gains as assessed by fluorescent in situ hybridization (FISH) with Her-2 protein overexpression by immunohistochemistry (IHC) in patients with Barrett's esophagus (BE) and esophageal adenocarcinoma (EAC). We analyzed 34 patients with Her-2 amplification and/or chromosome 17gains using FISH on brush cytology specimens. Seven patients (21%) showed high Her-2 locus amplification ( Her-2 : Cep17≥ 5 : 1), 5 (15%) showed low Her-2 locus amplification ( Her-2 : Cep17≥ 2< 5 : 1), and 22 (65%) displayed gains of chromosome 17 only. Further, we confirmed Her-2 amplification on corresponding biopsies that were taken at the same occasion as the cytologybrushings. Then, we compared the FISH results with IHC data obtained from the corresponding biopsies and showed that low level of Her-2 amplification does not correlate with Her-2 protein overexpression (score+ 3 /+ 2 ;P = 1 ), in contrast to the high amplification level (P = .001 ). Thus, in our population of BE and EAC patients, low level of Her-2 amplification does not result in detectable level of Her-2 protein as assessed by IHC.